THE DIET WHISPERER : 12-Week Reset Plan : Supercharge your metabolism, reverse diabetes and harmonise your brain clock - Chell, Paul Barrington, Dr.; Hope-Ross, Monique, Dr. (London : Yellow Kite, 2022)
Despite the overwhelming information about dieting, calorie counting and exercise, many of use still feel out of control. The authors share what they've learnt from decades of clinical practice helping patients to lose weight, and improve their physical and mental health. They dispel long-held myths about dieting, and instead use evidence-based medicine to show us why we gain weight, and teach us how we can fat adapt our bodies and reset our metabolism to lose weight quickly and permanently. You come away with a nutritional plan to set you on the road to reaching your target weight and start building a brighter, healthier future.
"Lose up to 12kg in 12 weeks" -- Cover.
Includes bibliographical references and index.
Keywords: Reducing diets; Nutrition; Weight loss; Metabolism; Reducing diets -- Recipes